[2]- e [3]rotaxanos como modelos para avaliar a influência das interações intercomponentes e intermoleculares no estado sólido cristalino - Orlando, Tainára (2021)
Rotaxanes are widely studied for their ability to move one component relative to another. Intercomponent interactions are widely studied in solution and have been gaining more field in the crystalline solid state. Intermolecular interactions in rotaxanes are still a field to be explored. This emphasizes the importance of studying intercomponent and intermolecular interactions to understand the behavior of these molecules in the crystalline solid state. Therefore, this thesis uses rotaxanes as models to understand the formation of different crystalline phases and evaluate the influence of intercomponent and intermolecular interactions in the crystallization process. For a series of rotaxanes containing Leigh-type macrocycle, self-assembly, solvates, and the formation of different polymorphic phases were evaluated. A new series of [2]- and [3]rotaxanes with two stations was synthesized and evaluated regarding intercomponent and intermolecular interactions. The studied rotaxanes showed similar general stages of crystallization, in which in the first stage there is the formation of one-dimensional nuclei and, in less cases, dimers. A wide molecular complementarity was observed, with a high contact area and a large number of interaction paths in the formed nuclei, which prevent the occurrence of specific interactions capable of directing the formation of crystals. This behavior can be explained by the intrinsic molecular topology of rotaxane molecules. The participation of the solvent during crystallization was evaluated and showed that the solvent can be easily trapped between the one-dimensional and dimeric nuclei during the last stages of crystallization. In one example, it was observed that its topology favored the entrapment of water molecules between the rotaxanes that form the one-dimensional nucleus in the first crystallization stage, and not because of the nuclei approximation. Initial insights into the contribution of solvents to the stabilization energy of solvates have been provided. Different polymorphic forms, with the solvent and temperature conditions to obtain each phase, were reported. The key to understand the existence of polymorphs at room temperature lies in the first crystallization nuclei to be formed, as both have similar stabilization energies at this point. The two-station thread allowed to obtain molecules of [2]- and [3]rotaxanes as a function of small modification in the stoppers groups. New parameters and approaches at the intercomponent and intermolecular level, to guide the interpretation of self-assembly, solvates, and polymorphs of rotaxane molecules, have been provided.